Discriminatory bullying : a new intercultural challenge - Elamé, Esoh (Springer Milan, 2013)
This book is devoted to the relation between bullying at school and ethnicity, gender, sexual orientation, and disability. In examining the interactions between bullying and discrimination, the authors set out from the premise that the current practice of intercultural education does not systematically address the issue of bullying, as evidenced by the lack, within schools, of intercultural education projects. The starting point for the work is a survey conducted in ten European countries on a sample of about 9,000 students including immigrants and natives. The research provides important information on which factors deserve special attention when formulating interventions in the classroom with the aim of preventing or combating discriminatory bullying. If intercultural education is called upon to handle the fight against any form of discrimination, it cannot shirk from addressing the issue of bullying discrimination. The results represent a sound, stimulating basis for broad and realistic reflections on discriminatory bullying and intercultural education, and show that intercultural pedagogy needs to be appropriately equipped theoretically. This book will be an indispensable tool for those seeking a thorough understanding of the new challenges facing intercultural education and the means of overcoming them. On that basis, innovative education practices should be developed with the aim of spreading a culture of non-violence and intercultural dialogue.